(untitled) (Archive of Conferences, 2021)
The article is devoted to highlighting the experience of primary school teachers in the introduction of the national-regional component in the aesthetic education of primary schoolchildren. It also pays attention to the pedagogical conditions of the effectiveness of aesthetic education and the specifics of multilevel education.